Analisis Daya Saing Ekspor Pinang Indonesia Di Pasar India - Marinda, Silvy Ayu; Tain, Anas; Mufriantie, Fithri (Universitas Galuh, 2024)
Areca nut is a plant from Palmaceae that can be utilized as industrial raw materials, pharmaceuticals, cosmetics, and textile dyes. Areca nut is one of the leading commodities in Indonesia's export activities. One of the countries that has great potential to become an areca export market is India. India is one of the largest areca importing countries in the world due to the high demand for areca in the country. The high level of competition today means that Indonesia must constantly improve its competitiveness to become a market leader. The purpose of this study is to analyze the level of competitiveness of Indonesian areca exports from 2003 to 2022 in the Indian market and analyze Indonesia's position as an exporter of areca nut or an importer of areca nut. The methods used for competitiveness analysis are Revealed Comparative Advantage (RCA) and Index of Trade Specialization (ISP). The results showed that the highest RCA value was in Myanmar at 146.33, in second place was Indonesia at 18.84, followed by Thailand 9.22, Singapore at 0.75, and in the last position was Malaysia at 0.32, although it has a different value but the five countries have a comparative advantage because the RCA value> 0. In the ISP analysis during 2013-2022 the highest value was in Indonesia at 0.999, followed by Myanmar 0.9786, Thailand 0.7108, Malaysia at 0.2134, and Malaysia at 0.2134, and finally Singapore at -0.0099. Indonesia and Myanmar are at the maturity stage, Thailand at the growth stage, Malaysia at the import substitution stage, and Singapore at the introduction stage. In an effort to increase the competitiveness of areca exports, it is necessary to increase production, in terms of quality and quantity, strengthen the supply chain, maintain price stability, trade policies, export regulations, and the role of the government in negotiating tariffs for entry fees to export destination countries.